Multikulturalisme pada Kelompok Sosial Karang Taruna Serdadu Desa Lumpang - Lazuardi, Fauzan; Fauzi, Agung (YASIN, 2022)
Indonesia is a vast country. Not only region but also in terms of culture, race, religion, and ethnicity. With this, Indonesia is clearly categorized as a plural country, in which there are various kinds of people in it. In response to this social conflict between a community group is unavoidable. Conflicts between religions, conflicts between races, conflicts between cultures, and conflicts between nations. Then multiculturalism becomes one of the efforts to prevent prolonged conflict. To support the goal of multiculturalism, the Serdadu youth group social group became the subject of research in this study. In this study, the researcher took a qualitative research method, with a phenomenological approach in which the researcher aimed to dig up information about the importance of the form of multiculturalism in the Serdadu youth group social group. This research was conducted in the community of Rw. 06 Lumpang Village This study found that (1) Making Pancasila the main foundation in carrying out community social activities. (2) To support the effectiveness of multiculturalism, it is necessary to have a view without differences in society (3) Unity is a priority in carrying out the multiculturalism process as a whole.